3 5/36
Пошаговое объяснение:
Задание.
Решите уравнение 6 11/12 - x = 3 7/9
Решение.
Чтобы найти неизвестное вычитаемое, надо от уменьшаемого отнять разность.
х = 6 11/12 - 3 7/9 = (6-3) + (11/12-7/9) = 3 + ((11*9 -7*12)/108) = 3 + (99-84)/108 =
= 3 + 15/108 = 3 5/36, или, что одно и то же, х = 3,13 (8) ≈ 3,14
ответ: х = 3 5/36
3 5/36
Пошаговое объяснение:
Задание.
Решите уравнение 6 11/12 - x = 3 7/9
Решение.
Чтобы найти неизвестное вычитаемое, надо от уменьшаемого отнять разность.
х = 6 11/12 - 3 7/9 = (6-3) + (11/12-7/9) = 3 + ((11*9 -7*12)/108) = 3 + (99-84)/108 =
= 3 + 15/108 = 3 5/36, или, что одно и то же, х = 3,13 (8) ≈ 3,14
ответ: х = 3 5/36